Mad Max beyond Thunderdome [videorecording (Blu-Ray)] - Ogilvie, George, 1931-; Gibson, Mel; Turner, Tina; Spence, Bruce; Miller, George, 1945 March 3- (Warner Home Video, 2013)
Max, a world-weary hero, stands alone against the barbarians of a post-nuclear Australia.